Perfil metabólico de vacas mestiças leiteiras uma semana pré- parto e durante o puerpério fisiológico - Oliveira, Raphael Soares de Barros Ramos (2011)
In order to know more about the energy metabolic profile of crossbred cows during the peripartum, blood samples were collected from 36 animals. For each type of metabolism is dosed serum concentrations of these metabolites: total proteins, albumin and globulin to the protein profile, calcium, phosphorus and magnesium for the mineral profile, AST, ALT, GGT and alkaline phosphates for the enzyme portion and finally, non-esterifies fatty acids (NEFA), ß-hydroxybutyrate (BHB), triglycerides, cholesterol and lipoproteins (VLDL, HDL and LDL) to the energy profile. The measurements were performed in seven different times (D-7, D0, D7, D14, D21, D28 and D43). The results of protein profile indicated a hypoproteinemia, both by albumin and globulin; the parturition demonstrated influence on the mineral profile, especially in the amounts of calcium, wich can be noted subclinical hypocalcemia, but nevertheless no animal showed symptoms for this disorder on clinical trials. The enzyme concentrations, did not represent any significant change, only AST during periods close to birth, showed an increase in its concentration. Finally, there was no significant changes to indicate severe energy deficiency, since there were no losses in the BCS and milk production is not influenced by the fact these animals are of low and medium production. It is concluded that probably the diet of these animals is lower in protein than necessary, have no energy deficit and liver damage and birth is influential on the mineral concentrations.